New Ways of Motivation in The Workplace - Hugge: Differences Between Generations and Countries - Iveta LUDVIGA; Joanna NIEŻURAWSKA-ZAJĄC; Carla PEREIRA; Nelson DUARTE (Communications of International Proceedings, 2021)
The objective of this practical study is to enrich current literature due to providing a new approach of employees’ motivation. Employees must be motivated in order to be effective at their workplace. Traditional motivators have been established, but several studies suggest that motivation is dwindling. We report the results of a survey based quantitative study conducted in Poland (n=1108), Latvia (n=729), and Portugal (n=432). In total 2269 responses were collected. Our sample consists of four generations: Baby Boomers, generation X, Millennials or generation Y and Generation Z. Finally, our study concluded that, there is a need to introduce new approach which will increase motivation at workplace.  We found that workplace aspects which can be characterised as Hugge are the most important workplace motivators. Interestingly that these aspects are especially important for Portuguese respondents
Keywords: : Employee Motivation; Hygge Concept; Human Resources; Generation Z; Exploratory Factor Analysis (EFA); Optimisation Model